La conmemoración de los 500 años de conquista española desde los pueblos indígenas de Chimborazo. - Ortega Altamirano, Erick Fernando (2018)
This research was carried out by observing some bibliographic contributions. They are very clear and specific, since it helps the researcher to link everything that occurred during 500 years of the Spanish conquest. According to several authors, the conquest of the new worlds, as they are known, Indians lived and suffered. Additionally, authors discus what they could do to be able to get ahead and be recognized as citizens. The Indians suffered many ferocious acts while being slaves, and entrusted. Peoples through the conquest had to adopt a religion that was not officially theirs. Evangelization was imposed to them, by which the conquerors dominated Indians. It promoted political, social, economic, religious and cultural changes. The present research project contributed to the analysis of the facts and the aspects and changes that the indigenous people had to go through around 500 years under Spanish conquest and indigenous resistance, for which they had to adopt a religion that was not officially theirs. They were discriminated and enslaved in their own lands and forcing them to work for the colonizers. They lived a stage of suffering as they were treated like animals or compared as they had a child's mentality.